Teknik Komunikasi Persuasif Pengurus Panti Asuhan Al Akbar Pekanbaru - Ermairel Salim (LPPM STISIP Persada Bunda, 2022)
The purpose of this study was to determine persuasive communication techniques for the administrators of the Pekanbaru Al Akbar Orphanage. Researchers used persuasive communication theory. This research method is descriptive with a qualitative approach. This research is a persuasive communication technique that needs to be applied to influence in a better direction. With persuasive communication techniques communicators can increase knowledge and change a person's attitude. Persuasive communication techniques are indispensable in conveying messages to children and adolescents. With persuasive communication techniques, communication becomes familiar, friendly, fun. Good persuasive communication techniques for children and adolescents are easy to digest the message content desired by communicators and motivate them at Al Akbar Orphanage Pekanbaru. The persuasive technique used is the management of the Al Akbar Orphanage using persuasive techniques, namely association techniques, integration techniques, reward techniques, ordering techniques so that the message conveyed by the Al Akbar Orphanage can be conveyed to foster children and can be digested properly so that they can be understood. guide and motivate foster children towards a better direction.